An Outbreak of Gastrointestinal Illness Associated with Khmer Noodles: A Multipronged Investigative Approach, Kandal Province, Cambodia, June 2014 - Kimsean, Panha; Sreng, Kosal; Has, Phalmony; Ly, Sowath; Sim, Sansam; Chhay, Sokheng; Prak, Dara; Bun, Sreng (OSIR Journal, 2017)
Food safety is a high priority for the Cambodian Ministry of Health, with standard operational procedures for foodborne diseases: intersectoral outbreak investigations and response finalized in 2015. On 29 Jun 2014, Kandal Provincial Health Department reported 143 patients with acute gastrointestinal illness, and 28 out of them were hospitalized. The number of patients increased to 215 within hours of the first report. A case-control study was conducted as well as laboratory testing, and an environmental survey to investigate the outbreak and institute necessary control measures. Three villages were randomly selected due to the provincial-wide distribution of the cases. A total of 37 cases and 36 controls were identified. Cases predominantly reported vomiting (97.3%) and diarrhea (75.7%). Consumption of Khmer noodles on 29 Jun 2014 was strongly associated with the illness (OR = 71.0, 95% CI = 8.6-582.2). Laboratory testing of food samples revealed Staphylococcus aureus and Bacillus cereus, which was consistent with the epidemiological and clinical findings. The investigation revealed the source as a sole local noodle producer and distributer. Environmental investigation of the noodle factory demonstrated multiple sources of contamination. The factory was temporarily shut down, and the team recommended destroying the remaining noodles. Local authorities were recommended to conduct regular inspection of the noodle factory.   Keywords: foodborne disease, disease outbreaks, gastroenteritis, Cambodia